Salaries, incentives and teaching intellectual production in the public university in Colombia - Sayago, Jhon Méndez; Azaf, Leonardo Vera (Universidad Pedagógica y Tecnológica de Colombia, 2015)
In this article the determinants of intellectual productivity of teachers of public universities in Colombia are studied, focusing on the effect of wage incentive on intellectual productivity and wage effects. Based on information from the teaching staff of the Universidad del Valle between the years 20042012, an econometric model lifecycle university professor were estimated to quantify these effects. An important and significant effect of the present value of the salary point was found, but no was found positive effect of wages on intellectual production. The effects of the incentive depending on the age of the researcher and the impact of percentage increases in the value of the salary point were also calculated.